The Erasure of Historical Consciousness and the Hegemony of the Present in Time Travel Films (ENTHYMEMA, 2025)
The paper discusses how the present became absolute and colonized the historical past in the mass culture of late capitalism, by examining the ideological premise of time travel films of the 1980s and 1990s. Drawing on Fredric Jameson’s and David Lowenthal’s views of history and popular culture, the article suggests that the primacy of the present and the disappearance of historical consciousness becomes really striking in narratives that thematize the unnatural structures and causal logics of multiple, co-existing temporal planes. The course of history is presented as an evolution towards superior social structures, culminating in the liberal democracy of the United States, and any interference with this system is portrayed as a threat to social order. Its hegemonic aspirations are glorified in the narratives through the affirmative attitude of the fictionalized historical characters towards it.
Keywords: Sci-Fi; Time Travel; Popular Imagination; Historical Consciousness; Presentism; Americanism